2019
DOI: 10.1186/s12935-019-0975-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed circRNAs and a novel hsa_circ_0000144 that promote tumor growth in gastric cancer

Abstract: Background Circular RNAs (circRNAs) are involved in regulating tumor pathogenesis. The mechanism of circRNAs in gastric cancer (GC) is still unknown. Our study aimed to identify differentially expressed circRNAs and assess a novel circRNA (hsa_circ_0000144) in the proliferation, migration, and invasion in GC. Methods Gene ontology (GO) enrichment and analyses of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, pathway network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Dozens of circRNAs have been announced to participate in the progression of GC cells. For example, the novel circ_0000144, circOSBPL10 and circHECTD1 were upregulated in GC, and silencing of them could inhibit human GC cell proliferation, migration and invasion in vitro and in vivo [16][17][18]. The other tumor-related physiological processes had also been modulated by dysregulation of circRNAs, such as cell apoptosis, autophagy, Warburg effect, glutaminolysis, EMT, and cisplatin resistance, as well as the underlying signaling pathways [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of circRNAs have been announced to participate in the progression of GC cells. For example, the novel circ_0000144, circOSBPL10 and circHECTD1 were upregulated in GC, and silencing of them could inhibit human GC cell proliferation, migration and invasion in vitro and in vivo [16][17][18]. The other tumor-related physiological processes had also been modulated by dysregulation of circRNAs, such as cell apoptosis, autophagy, Warburg effect, glutaminolysis, EMT, and cisplatin resistance, as well as the underlying signaling pathways [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The luciferase reporter assay con rmed that hsa_circ_0089153 sponged hsa-miR-145 to mediate upregulation of ZEB2 expression, thereby playing a carcinogenic role in PTC. hsa_circ_0089153 was also reported to be upregulated in gastric cancer and bladder cancer [25,26]. Our study indicated that upregulated hsa_circ_0089153 may sponge hsa-miR-139-3p, and upregulated SPC24 and CDKN2A expression to promote PTC progression.…”
Section: Discussionmentioning
confidence: 59%
“…All cells were cultured at 37 °C for 18-24 h in a humidi ed incubator containing 5% CO 2 . The expression level of hsa_circ_0065898 was tested by quantitative PCR (qPCR), as described in a previous study [7].…”
Section: Cell Culturementioning
confidence: 99%
“…Some reports have shown that circRNAs are involved in various human diseases, particularly cancers [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%